Finansowanie międzynarodowych trybunałów karnych - Krzan, Bartłomiej (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
This paper aims at a thorough analysis of financing international criminal tribunals and courts. This aspect, despite being rather technical in character, is of crucial importance for the proper, successful operation of these institutions. There are different methods of providing funds, which draw on the very establishment of the international criminal tribunals. However, a common denominator is their reliance, albeit to a different extent, on the financial resources of the United Nations, combined with voluntary contributions. All tribunals face problems with funding, which might also result in jeopardising their independence. Reducing the costs of international criminal justice may easily lead to a situation where judicial standards, including fairness and impartiality, would be put at stake.
Keywords: trybunał karny; sądownictwo międzynarodowe; finansowanie; Międzynarodowy Trybunał Karny